1970
DOI: 10.3329/jbau.v6i2.4842
|View full text |Cite
|
Sign up to set email alerts
|

Rural women and poverty: A study on the role of RDRS for poverty alleviation in Bangladesh

Abstract: No development objectives can be achieved without making women self reliant. The present study deals with the role of Rangpur Dinajpur Rural Service (RDRS) on poverty alleviation and women empowerment in Kaligonj upazila under Lalminirhat district considering their participation in different programmes of RDRS. The impact of the study was assessed in terms of economic and social gains accrued by the women's and their families' activities. The random sampling technique was used for selection of sample size. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Numerically, Shetty (2010) found that 52% of plan recipients in Chennai, India had reported an increase in their level of income due to their access to loans and small grants. In addition, Islam et al (2008) illustrated that the percentage living below the poverty line was lower than the national average which means that there was a reduction of poverty amongst the study group because they joined Rangpur Dinajpur Rural Service. These data show that the participation of women in this program improved their economic standing and sustainability just as Sindhe et al (2013) and Shetty (2010) had argued above.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerically, Shetty (2010) found that 52% of plan recipients in Chennai, India had reported an increase in their level of income due to their access to loans and small grants. In addition, Islam et al (2008) illustrated that the percentage living below the poverty line was lower than the national average which means that there was a reduction of poverty amongst the study group because they joined Rangpur Dinajpur Rural Service. These data show that the participation of women in this program improved their economic standing and sustainability just as Sindhe et al (2013) and Shetty (2010) had argued above.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In her findings, Shetty (2010) concluded that the two microcredit programs had a small impact on poverty reduction on the basis of credit alone but that they allowed women to access low-interest loans that they otherwise wouldn't have been able to access. On the contrary, Islam et al (2008) established that in Bangladesh women in the RDRS program tried to improve their economic conditions by using credit in order to diversify their sources of income, which led to a notable improvement in their living standard and an improvement in their livelihood. As with Islam et al (2008), Sindhe et al (2013) stated that their participation in economic activity allows women to obtain new skills and further interact in their society, which would improve their social standing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations